Bone marrow's harvest in the coxal tuberosity for isolation and culture of mesenchymal stem cells of buffaloes (Bubalus Bubalis) - Oba, Eunice [UNESP] (2013)
Several studies with mesenchymal stem cells (MSCs) have been developed in many species because of its ability to differentiate into other mesoderm lineages, capacity of self-regeneration, low immunogenicity, paracrine, anti-inflamatory, immunomodulatory and antiapoptotic effects which make then a promissory source to be used in therapeutic strategies. The aim of this study is to report the technique of harvest of bone marrow (BM) in the coxal tuberosity (CT) of buffaloes. For this, the animals were selected, identified and contained in a stock. Then trichotomy was performed in the region corresponding to the CT. After identifying the anatomic site it was performed antisepsis, local anesthetic block and introduction of a myelogramś needle (Lang ®) for BM aspiration. Once the needle was firmly fixed in the CT, the mandril was removed and proceeded to BM aspiration with a syringe (20 mL) containing 1 ml of heparin at 1000 IU/mL and 1 mL of PBS. After the collection, each sample collected was manually homogenized, identified and referred to the LRACT - FMVZ/UNESP-BRAZIL for the correct processing. The anatomical site tested showed to be an alternative site of harvest of BM once provided the appropriate isolation and culture of the mononuclear fraction. Moreover, the procedure was performed without difficulty and with great security. Based on this, it can be conclude that CT is an excellent anatomical site for isolation and culture of MSCs and the proposed technique is viable and feasible to be held in buffaloes.